The Nexus between Green-Blue Economy and Islamic Finance on Logistics Performance: Evidence from OIC Countries - Lestari, Winda Rika; Wahyudi, Heru; Yahya, Ja’far Muhammad; Leny, Sandra Mei (International Journal of Economics and Financial Issues, 2025)
The global transformation towards sustainable development has encouraged the integration of Islamic finance, green economy, and blue economy as alternative models of economic development. Organization of Islamic Cooperation (OIC) countries face the challenge of optimizing logistics performance amid significant regional disparities, with global Islamic finance industry assets reaching USD 3.38 trillion by 2023 but the majority of OIC countries still show suboptimal Logistics Performance Index (LPI) scores. This study aims to analyze the influence of Islamic finance, green economy, and blue economy on the logistics performance of OIC countries, with the hypothesis that the integration of the three dimensions simultaneously improves the efficiency of the national logistics system. The study uses a panel data regression model with Logistics Performance Index as the dependent variable, as well as Islamic Banking Assets as a proxy for Islamic finance, Renewable Energy Consumption as a proxy for green economy, and Container Port Traffic as a proxy for blue economy. The estimation results show that Islamic Banking Assets has a significant positive effect (β = 0.002423, P < 0.05), Container Port Traffic has a significant positive effect (β = 2.10E-08, P < 0.01), but Renewable Energy Consumption has a significant negative effect (β = −0.007024, P < 0.01) on logistics performance. The model explains 30.33% of the variation in LPI with simultaneous significance at α = 5% level. The findings indicate that Islamic banking asset development and container port infrastructure support logistics performance, while renewable energy transition requires a longer adaptation period to produce positive effects on logistics efficiency of OIC countries.